Evaluating New Zealand's restorative promise: the impact of legislative design on the practice of restorative justice. (2nd January 2020) - Pfander, Sarah Mikva
ABSTRACT: Restorative justice is regarded in modern criminal justice systems as one approach to address inadequacies in the conventional justice model. New Zealand has become a leader in implementing legislatively mandated restorative procedures. This reputation is due in part to a handful of supportive statutes: the Sentencing Act 2002, the Victims' Rights Act 2002, the Parole Act 2002, the Corrections Act 2004 and subsequent amendments to those acts. In this article, I evaluate the practices bolstered by these acts and how effectively they operate, accounting for how legislative design may contribute to achievements and shortcomings in New Zealand's restorative justice programmes. I supplement the results by comparing New Zealand's efforts to those in Vermont, a U.S. state similarly well-regarded for its restorative policies. The evaluation of each jurisdiction's restorative justice programme is based on metrics for restorative success from Bazemore and Schiff (2005. Juvenile justice reform and restorative justice: building theory and policy from practice. Cullompton: Willan Publishing). I employ qualitative and quantitative data, surveying existing evaluations of restorative justice in New Zealand and Vermont, collecting longitudinal statistics, and conducting interviews with restorative justice practitioners. Overall, this analysis reveals that the design of restorative justice programmes requires negotiation; it is difficult to balance the dimensions of effective restorative justice with the needs of modern justice systems.